RANCANG BANGUN ALAT PEMBERI PAKAN KUCING OTOMATIS MENGGUNAKAN MIKROKONTROLER NODEMCU BERBASIS INTERNET OF THING (IoT) - Regar Devitasari; Kurnia Paranita Kartika (Antivirus : Jurnal Ilmiah Teknik Informatika, 2020)
The implementation and utilization of the Internet of Things in the world of electronics have been very numerous and are still growing. The function of the IoT itself is to simplify human work, monitor various equipment remotely, and increase the effectiveness of tools. In this study, a tool was made to monitor and provide feed to pet cats that can be accessed remotely by the user. The background of making this tool is due to several things in cat maintenance activities, such as irregular feeding schedules, difficulty controlling pet development, difficulty controlling feed availability, difficulty calculating feed requirements, and frequent breeders doing other activities or work outside the home. The method used in this research is the Research and Development method. The advantage or performance of this tool lies in the combination of several automatic functions which include feeding and notification. The combination of some of these functions includes the existence of a NodeMCU microcontroller that is integrated with the internet network, and this automation tool can provide real time feed by utilizing the RTC component which can set the time when the feed will be given. Users will also get direct notifications via Foxpush without having to open a web page to find out whether the feed has been completed or not. After performing various tests, the average success rate of the whole system was 68%.